Investor Behavior towards Risk – Return in Capital Markets - R, Lakshmi; Chiranjeevi; H S , Naveen Kumar (The journal of contemporary issues in business and government, 2023)
The financial industry plays a significant role in capital markets and has aroused increasing managerial and academic interests in recent decades. Individual investors are becoming more cautious towards financial investment which makes it difficult for financial service providers to formulate marketing strategies after experiencing several financial crises. Prior research has suggested that financial investment behaviour would be affected by various factors, including the demographic characteristics of individuals. The objective of the study is to study the perceptions and awareness of the investors about the stock markets and to determine the impact of investors’ behavioral influences on Risk – Return management and Effective investment decision. Primary data collected through questionnaire and used ANOVA and Chi-square test for analysis. Study concluded that the factors i.e Risk-Return management, Investment awareness, Monitoring & evaluation significantly influence on the Effective investment decision.